1987
DOI: 10.2466/pms.1987.64.3c.1147
|View full text |Cite
|
Sign up to set email alerts
|

Selected Sleep Disturbances in School Children Reported by Parents: Prevalence, Interrelationships, Behavioral Correlates and Parental Attributions

Abstract: Epidemiological, behavioral and etiological variables related to sleep disturbances were investigated in a survey of 1695 children in Grades 1 to 12 from 11 randomly selected schools. Sleep-walking, nightmares and sleep-talking were strongly associated with each other as well as to a family history of sleep-walking. Enuresis, however, was not related to the other sleep variables. Socioeconomic status of father was weakly related to enuresis and sleep-talking but not to sleep-walking or nightmares. Gender was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 18 publications
6
34
1
3
Order By: Relevance
“…However, our data do not allow for speculations about a possible relation between these reversed developments because of the small sample size. Incidence of nightmares (any type) for children without ASD / PTSD (varying between 16% ten days and 32% two months postaccident) was roughly comparable to a large scale study by Fisher and Wilson (1987).…”
Section: Nightmares and Psychopathologysupporting
confidence: 66%
“…However, our data do not allow for speculations about a possible relation between these reversed developments because of the small sample size. Incidence of nightmares (any type) for children without ASD / PTSD (varying between 16% ten days and 32% two months postaccident) was roughly comparable to a large scale study by Fisher and Wilson (1987).…”
Section: Nightmares and Psychopathologysupporting
confidence: 66%
“…4,24,38,39 As also noted in previous studies, 24,40,41 it was found that sleepwalking commonly begins in childhood and less frequently in adolescence. In addition, in most cases, the condition is outgrown before the age of 10 years.…”
Section: Sleepwalkingsupporting
confidence: 50%
“…Finally, numerous studies have shown that family disruption, low parental education, or low social class are positively associated with the presence of parasomnias, especially to enuresis. 6,13,[23][24][25][26] There have been many studies on the prevalence of a single parasomnia in large samples of randomly selected normal children, but this is the first study to evaluate simultaneously the prevalence of the most frequent parasomnias in a large, randomly stratified sample of normal children with the same methods of investigation. The major aims of this study were: 1) to document the prevalence and developmental aspects of the most frequent parasomnias in the same children between 3 and 13 years of age, and 2) to assess gender differences, relationships between parasomnias, and associations with anxiety and family adversity in 11-year-old children.…”
mentioning
confidence: 99%
“…As reported in previous studies, nightmare frequency was related to the occurrence of other parasomnias (e.g., [11,32]), sleep problems (e.g., [10,27]) and waking-life psychopathology (see introduction). The highest correlation was found for the emotional problems score of the SDQ which encompasses the occurrence of headaches, worries, anxieties and being unhappy and nervous.…”
Section: Discussionmentioning
confidence: 65%